Experimental comparison of NACA airfoils and KFm-2 variants using wind tunnel testing to analyze lift and drag characteristics - Maurath, Riley (My University, 2024)
Kline-Fogleman airfoils were created in the hopes of creating an airplane that could handle turbulence, climb higher, and recover after stalling. Experimental research was conducted in order to better understand how the Kline-Fogleman step feature affects NACA airfoils; in particular, their lift, drag, and stall characteristics. A simplified airfoil theory can be used to determine lift, drag and pitching characteristics of standard airfoils. One goal of this work was to see how accurate this simple theory is when dealing with more complex airfoil profiles, and to see if an effective chamber could be determined as a useful parameter or characteristic. Various airfoils (NACA 0012, KFm 0012, NACA 4412, and KFm 4412) were made utilizing the concept of rapid prototyping to determine the best settings and orientation for the final wings, which were designed and 3-D printed using ASA plastic. The testing was conducted in an Aerolab wind tunnel, which was instrumented with an electronic strain gauge balance and generated with a LabVIEW interface. The wind tunnel allowed for the opportunity to compare the calculated lift, drag and pitching moment, with experimental results that were obtained over a range of angles of attack and two different airspeeds. This project demonstrated the possibility of determining basic lift and drag values for more complex airfoil shapes that contain unique features like the KFm steps. No evidence was found to conclude that KFm airfoil provided better flight characteristics. A simplified theory calculated the effective camber height of the KFm airfoils to within 0.03 and 0.06 inches of the NACA variants’ camber height. This caused the zero-lift angle of attack to be greater for the KFm wings versus the NACA wings.
Keywords: Airfoil; Kline-Fogleman; Aerodynamics; NACA; Lift; Drag